Polyphenolic Extract from Tarocco (Citrus sinensis L. Osbeck) Clone “Lempso” Exerts Anti-Inflammatory and Antioxidant Effects via NF-kB and Nrf-2 Activation in Murine Macrophages - Pepe, Giacomo (Nutrients, 2018)
Citrus fruits are often employed as ingredients for functional drinks. Among Citrus, the variety, “Lempso”, a typical hybrid of the Calabria region (Southern Italy), has been reported to possess superior antioxidant activity when compared to other common Citrus varieties. For these reasons, the aim of this study is to investigate in vitro the nutraceutical value of the Tarocco clone, “Lempso”, highlighting its anti-inflammatory and antioxidant potential. A post-column 2,2′-diphenyl-1-picrylhydrazyl (DPPH•) radical scavenging assay for the screening of antioxidant compounds in these complex matrices was developed. Subsequently, polyphenolic extract was tested on a murine macrophage cell line under inflammatory conditions. The extract resulted was able to significantly inhibit nitric oxide (NO) and cytokine release and inducible nitric oxide synthase (iNOS) and cycloxygenase-2 (COX-2) expression. The inhibition of these pro-inflammatory factors was associated to Nuclear factor-kB (NF-kB) inhibition. Our results also indicate an anti-oxidant potential of the extract as evidenced by the inhibition of reactive oxygen species (ROS) release and by the activation of the nuclear factor E2-related factor-2 (Nrf-2) pathway in macrophages. The obtained results highlight the anti-inflammatory and antioxidant potential of Lempso extract and its potential use, as a new ingredient for the formulation of functional beverages with high nutraceutical value, providing health benefits to consumers.